Educating children and young people with acquired brain injury - Walker, Sue 1954-; Wicks, Beth (Routledge, 2018)
"Educating Children with Acquired Brain Injury is an authoritative resource book on the effects of brain injury on young people and how educators can understand and support their needs. This new edition has been updated to reflect changes to legislation and practice relating to special educational needs and will enable you to maximize the learning opportunities for young people with acquired brain injury (ABI). Considering key areas in special educational needs such as communication, interaction, cognition, sensory and physical needs, the book provides information on the multifaceted needs of children and young people with ABI and how these needs can be met. This book will help you to:Understand the difficulties that young people with ABI experience Support these students by using appropriate strategies to help their learning Understand and address the social and emotional difficulties experienced by these students Work in partnership with families and other professionals Understand information from other professionals by reference to a glossary of terms Access further useful information from relevant resources and organisations Written for SENCOs, teachers, teaching assistants, educational psychologists and other education professionals across all settings, Educating Children with Acquired Brain Injury is full of useful information and advice for parents and other family members, clinical and behavioural psychologists, therapists and support workers involved with children and young people with ABI."--Provided by publisher